STUDI KELAYAKAN PEMBANGUNAN KOLAM RETENSI DI WILAYAH KECAMATAN SUKARAMI KOTA PALEMBANG - Gumelar, Anjas; Susanti, Susi; Islami, Fajar Sadik; Permatasari, Rosmalinda (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2024)
Water runoff is temporarily stored in retention ponds as part of a flood control scheme to avoid major floods. There are currently a number of retention ponds in Palembang City that work to reduce flooding during rainy seasons. Land use is expanding, and water catchment areas are getting smaller as a result. The feasibility of constructing a retention pond in Palembang City's Sukarami District is discussed in this study. The usability, hydrology, and physical environmental aspects of data analysis are the main areas of study. The study of hydrological aspects indicates that the planned retention pond has an area of 6.55 Ha and is capable of accommodating a large water discharge of 0.294 - 0.466 m3/sec for a return period of 50 years. The research also demonstrates the benefits of collecting rainwater runoff and improving environmental aesthetics. The construction process and the presence of this retention pond will have an impact on environmental quality, according to the findings of the study of physical environmental elements.